Association between changes in thyroid hormones and incident type 2 diabetes using joint models of longitudinal and time-to-event data: more than a decade follow up in the Tehran thyroid study - Amirabadizadeh, Alireza; Mehran, Ladan; Amouzegar, Atieh; Asgari, Samaneh; Khalili, Davood; Azizi, Fereidoun (Frontiers in Endocrinology, 2024)
Background: Type 2 diabetes mellitus (T2DM) poses a significant public health challenge, contributing to considerable morbidity and mortality worldwide, which necessitates urgent preventive measures. Thyroid disorders, prevalent in many individuals, are intricately linked to metabolic health, yet studies on their relationship with T2DM yield inconsistent results—some suggesting an increased risk with abnormal thyroid hormone levels, while others indicate potential protective effects.This study investigated the association between changes in serum thyroid-stimulating hormone (TSH) and free thyroxine (FT4) levels and the incidence of type 2 diabetes mellitus. Methods: Data from 1938 individuals aged ≥20 in the Tehran Thyroid Study cohort were used, spanning four examination cycles from 1999 to 2012, with three-year intervals. TSH and FT4 levels were log-transformed and modeled as time-varying exposures to study their association with incident T2DM. Results: During a median follow-up of 9.43 years, 135 new T2DM cases were identified. The multivariable-adjusted joint model (JM) revealed that each unit increase in log-transformed TSH level was associated with a 25% decrease in T2DM incidence [HRs (95% CI): 0.75 (0.64-0.90)]. Conversely, each unit increase in FT4 level showed a marginally significant higher risk [1.06 (0.99-1.13); p-value=0.06]. Conclusion: The findings of this study suggest that dynamic changes in serum thyroid hormones are associated with the development of T2DM. Rising TSH and decreasing FT4 over time are associated with a lower risk of diabetes. These findings suggest a complex interplay between thyroid function and the risk of T2DM, emphasizing the importance of monitoring thyroid hormone levels as a part of T2DM prevention strategies.